DNA-binding antibodies and hepatitis B markers in acute and chronic liver disease. - Kingham, J G (1978)
A Farr technique has been used to assay antibodies to double-stranded DNA in the serum of patients with acute and chronic liver disease and carriers of HBsAg from the United Kingdom and Iraq. These antibodies were found in all groups from both countries. The highest levels were found in chronic active hepatitis and cirrhosis. In the Iraqi patients there was a strongly positive correlation between DNA-binding antibody levels and the presence of hepatitis B markers but not with disease activity. In the patients from the United Kingdom there was little correlation with disease activity and none with autoantibodies. Ninety-five per cent of asymptomatic carriers of HBsAG had elevated DNA-binding antibodies. It is suggested that hepatitis B-specific DNA might be one trigger to DNA antibody formation, though in liver disease a variety of factors are clearly operative.